2014
DOI: 10.1101/006031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing the Toxicofera: comparative reptile transcriptomics casts doubt on the single, early evolution of the reptile venom system

Abstract: Background The identification of apparently conserved gene complements in the venom and salivary glands of a diverse set of reptiles led to the development of the Toxicofera hypothesis – the idea that there was a single, early evolution of the venom system in reptiles. However, this hypothesis is based largely on relatively small scale EST-based studies of only venom or salivary glands and toxic effects have been assigned to only some of these putative Toxcoferan toxins in some species. We set out to investiga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 108 publications
1
23
0
3
Order By: Relevance
“…However, the downside of these qualities is that it has also avoided scrutiny and testing. There have recently been several studies which have cast doubt on the Toxicofera hypothesis (Hargreaves et al 2014a;Reyes-Velasco et al 2015), although their interpretation has led to alternative conclusions. Several phylogenetic analyses incorporating non-venom gland transcriptomic data have shown that non-toxin sequences nest within clades of toxin genes, and it has been acknowledged that such findings provide ".…”
Section: Casting Doubt On the Toxicofera Hypothesismentioning
confidence: 94%
See 2 more Smart Citations
“…However, the downside of these qualities is that it has also avoided scrutiny and testing. There have recently been several studies which have cast doubt on the Toxicofera hypothesis (Hargreaves et al 2014a;Reyes-Velasco et al 2015), although their interpretation has led to alternative conclusions. Several phylogenetic analyses incorporating non-venom gland transcriptomic data have shown that non-toxin sequences nest within clades of toxin genes, and it has been acknowledged that such findings provide ".…”
Section: Casting Doubt On the Toxicofera Hypothesismentioning
confidence: 94%
“…A large scale test of the robustness of this hypothesis found that many Evolution of Venomous Animals and Their Toxins DOI 10.1007/978-94-007-6727-0_4-1 # Springer Science+Business Media Dordrecht 2015 of the genes used to support the single, early evolution of venom in squamates are in fact expressed in multiple body tissues including the salivary gland of a non-Toxicoferan lizard, the leopard gecko (Eublepharis macularius) (Hargreaves et al 2014a). No evidence has been found of either a venomspecific splice variant or significantly elevated expression level in the venom or salivary gland.…”
Section: Casting Doubt On the Toxicofera Hypothesismentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, in the Toxicofera, the venom appears to have evolved before the delivery system (although see [6] for an alternative view of venom evolution in reptiles).…”
Section: Meiacanthusmentioning
confidence: 99%
“…Thus recent reviews that relied on the Hsiang et al trees to reconstruct the evolutionary history of the organisms and also the associated venom systems inherit the problems of the original study (Mackessy et al, 2016;Sweet, 2016). Both Mackessy and Sweet also relied heavily upon Hargreaves tissue expression paper (Hargreaves et al, 2014) for their interpretation. For the exact differences between the traditional and Toxicofera phylogenetic approaches we recommend looking into dedicated studies (Streicher and Weins, 2016;Mackessy et al, 2016;Jackson et al, 2016;Zheng and Weins, 2016;Vidal and Hedges, 2009;Townsend et al, 2004).…”
Section: Toxicoferamentioning
confidence: 99%